FOOD AND BEVERAGE DEPARTMENT CUSTOMER SATISFACTION - Linda, Tina; Herawati, Anis; Kanwo, Kanwo; Santoso , Widodo Heru (AGUSPATI Research Institute, 2020)
Hospitality is the largest and fastest growing industry in the world. The hospitality industry offers the best service and the best foods which provide in the restaurant. Many ways are done to increase the quality of service and food in the restaurant industry to get customer satisfaction. Food and beverage department has important responsibility to maintain the quality of the food and beverage sercice and product as well. Consumer behavior is the decision making process by customers in selecting, buying, using and taking an advantage of product service or either experience in order to satisfy the needs and desire for customers. In this research the writer will discuss about customer behavior in opal coffee medan that aims to know more about customer’s characteristic and how to deal with them in order to give customer satisfaction. Based on the research the writer will discuss about the regular guest who visited Opal coffee and get the interview about how the customer perception about staff’s services and the solution that might be used as an input to the company.. Method for this research is qualitative. Sampling technique using the snowball technique. The result is expected to able to give a boost for the company to resolve the problem and improve the quality service that aims to get customer satisfaction. Keywords – service quality, customer behavior, customer satisfaction, food and beverage